Documentation of pharmacotherapeutic interventions of pharmacy students - King ED; Wilson MA; Van L; Emanuel FS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
During patient care rounds with the medical team, pharmacy students have made positive contributions for the benefit of the patient. However, very little has been documented regarding the impact these future healthcare professionals are making while on clinical rotations.The objective of this study was to assess the impact that clinical interventions made by 6th year pharmacy students had on overall patient outcome. Using a special program for a personal digital assistant (PDA), the students daily recorded the pharmacotherapeutic interventions they made. The interventions ranged from dosage adjustments to providing drug information. Data was collected over a 12-week period from various hospitals and clinics in the Jacksonville, Florida area.In total, there were 89 pharmaceutical interventions performed and recorded by the students. Fifty interventions involved drug modification and fifty-four interventions were in regards to drug information and consulting. Of the drug information and consulting interventions, 15 were drug modification.This study shows the impact pharmacy students make in identifying, recommending, and documenting clinical pharmacotherapeutic interventions. Similar to pharmacists, pharmacy students can also have a positive contribution towards patient care.